1991
DOI: 10.1063/1.350381
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Dynamical x-ray diffraction from nonuniform crystalline films: Application to x-ray rocking curve analysis [J. Appl. Phys. 5 9, 3743 (1986)]

Abstract: Erratum: Rocking curve peak shift in thin semiconductor layers [J. Appl. Phys. 66, 985 (1989)] The statement "a wrong boundary condition, saying that the amplitude X is zero deep inside the substrate crystal" on page 986 is incorrect. In fact, our boundary condition Eq. (2) can be obtained from Halliwel's analytical formula for a single-crystal layer' by setting X = 0 at the back side of the crystal layer and assuming the layer thickness to be infinite in her formula. Therefore, our Eq. (2) and the above bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 0 publications
1
41
0
Order By: Relevance
“…In particular, the diffraction intensity depends on both the the amplitude of a particular acoustic wavevector (A(q)) as well as the phase (φ m ) of the acoustic mode. Several computational methods have been developed which can calculate the x-ray rocking curve due to a known the crystalline structure profile 31,35,36 , however, a direct inversion from a single x-ray diffraction peak is quite difficult. In cases where the one-dimensional strain is both static and monotonic, it has been shown that the diffraction pattern can be uniquely inverted to reveal the strain profile 37 .…”
Section: B Time-resolved X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the diffraction intensity depends on both the the amplitude of a particular acoustic wavevector (A(q)) as well as the phase (φ m ) of the acoustic mode. Several computational methods have been developed which can calculate the x-ray rocking curve due to a known the crystalline structure profile 31,35,36 , however, a direct inversion from a single x-ray diffraction peak is quite difficult. In cases where the one-dimensional strain is both static and monotonic, it has been shown that the diffraction pattern can be uniquely inverted to reveal the strain profile 37 .…”
Section: B Time-resolved X-ray Diffractionmentioning
confidence: 99%
“…This superposition can be demonstrated by numerically calculating x-ray rocking curve of a strained crystal. To model the diffraction pattern of a longitudinal strained crystal, we use the diffraction algorithm developed by Wie et al 31 . This algorithm numerically solves the Takagi-Taupin equations 32-34 governing dynamical xray diffraction for perfect crystals with a strained surface.…”
Section: A One-dimensional X-ray Diffractionmentioning
confidence: 99%
“…The lack of inversion symmetry in InSb is ignored, except in the determination of the structure factor for the 222 reflection. The rocking curves are calculated for a particular strain profile using the method given by Wie et al [23]. The strain is calculated using the model of Thomsen et al [15], who solved the elastic equations for an instantaneous and exponentially decaying stress due to short-pulse laser absorption.…”
Section: (Received 28 November 2000)mentioning
confidence: 99%
“…Calculation of the rocking curve for an arbitrary semiconductor heterostructure is based on the solution of the Takagi-Taupin equation [4][5][6][7] for dynamical diffraction,…”
Section: Theorymentioning
confidence: 99%
“…Dynamical [1][2][3][4][5][6] and kinematical [7][8][9][10][11] simulations have been used in conjunction with a curve-fitting procedure to extract the profiles of strain and composition, but are based on perfect, dislocation-free laminar crystals, and this renders the analysis inapplicable to mismatched structures with dislocation densities greater than 10 6 cm À2 . Krivoglaz and Ryaboshapka 12 and Levine and Thomson 13 have analyzed the line profiles of Bragg peaks from crystals containing straight, parallel screw dislocations with precisely known atomic displacements.…”
Section: Introductionmentioning
confidence: 99%